RĂSPUNDEREA JURIDICĂ ÎN DREPTUL COMUNITAR AL AFACERILOR - Valerica Nistor (EIRP Proceedings, 2006)
The communitary responsibility is a principle of the communitary law according to which any breach of a liability leads to the judicial responsibility for some offences, having as a consequence the paying of damages. According to the theories of the communitary law, the judicial responsibility of a state may have as a basis the committing of an international offence, action or non-action, which breaches the norms and principles of the international law, or of an international offence, a very serious one, causing prejudices both to a state and to the European community as a whole.